Tra le maglie della rete. Aree interne, anarchivio e pedagogie radicali per un’estetica del capitale turistico - Bosca, Paolo (Scenari, 2025)
This article reflects on the ways in which the phenomenon of archiving cultural elements, which is essential for the acquisition of touristic capital in the global market, is transformed in the context of so-called inland areas. I will try to highlight how the idea of the anarchive, in the elaboration offered by The SenseLab, is particularly fertile for these kinds of areas. Alongside this practical-theoretical device, I will take some elements of the Global Tools research, carried out in the 1970s by a group of architects and theorists who, provocatively abandoning cities, turned to rural areas to configure a pedagogical practice that coincided with life, moving away from any idea of detached fruition. In conclusion, I will offer an example of the anarchiviation of inland areas: Reminescenza by the collective Spazio Vacante. A concrete cue for the creation of tourist surplus value rooted in the life that flows even where it seems to have stopped long ago.